Anatomic Landmarks for Minimally Invasive Exposure for Flexor Digitorum Longus (FDL) Tendon Transfers and Spring Ligament Reconstruction - Sarah E. Black; James R. Jastifer MD; Joseph Brunejes MD (Foot & Ankle Orthopaedics, 2022)
Category: Other; Basic Sciences/Biologics; Hindfoot; Midfoot/Forefoot Introduction/Purpose: The approach for identification of the FDL tendon is classically described through an incision proximal to the medial malleolus extending past the navicular following the inferior border of the first metatarsal.1This incision is lengthy, and we believe that the navicular tuberosity, medial malleolus, and/or sustentaculum tali can be used as reliable landmarks for identification of the FDL more precisely and reliably. The purpose of this study is to detail spatial anatomy of the medial arch to allow for a more reliable and less invasive exposure of the FDL. Methods: Ten cadaver specimens were used for a total of 20 extremities. Anatomic locations were identified and pinned with the foot positioned in neutral dorsiflexion. Anatomic locations pinned included tip of the anterior colliculus, navicular tuberosity, proximal portion of the sustentaculum tali, and the distal portion of the sustentaculum tali. Photographs were taken of each cadaveric specimen with pins in place. Image J calibrated software was then used to calculate the distance between anatomic points. Averages were calculated for all measurements. Results: On average the superior margin of the sustentaculum tali was located 8 mm from the FDL with a range of 5-15 mm. Average distance from inferior sustentaculum tali to the FDL was 9 mm with a range of 5-12 mm. Average distance from medial malleolus to superior FDL was 18 mm with a range of 11-27 mm. Average distance from medial malleolus to inferior FDL was 27 mm with a range of 20-36mm. Average distance from navicular tuberosity to anterior FDL was 22 mm with a range of 11-27 mm. Average distance from navicular tuberosity to posterior FDL was 30 mm with a range of 19-42 mm. Conclusion: The 'lighthouse' for the harvest of the FDL tendon is the sustentaculum tali. Intraoperatively, the FDL tendon is found 22-31 mm directly posterior to the navicular and 18-27 mm inferior to the medial malleolus. This provides a reliable anatomic region where a 40 mm oblique approach can be made to access the FDL and spring ligament complex for a more minimally invasive approach in all of the studied specimen.